Forms of canonization of the Colombian novel in the literary histories (1908 - 2006) (2009)
Although criticized, even discredited, the canon concept in its catalog of perfection (a list of truly sacred texts) is actively maintained by literary readers, teachers and researchers. The type of question arises by the time you read a prescriptive manu